Point heat sink induced by droplet train impingement - Qiu, Lu (2017)
A point heat sink is produced by impinging a high frequency microscale droplet stream onto a superheated copper substrate. Although the overall target surface area is larger than the liquid-solid interface by two or three orders of magnitude, the thermal energy is mainly removed through the point heat sink rather than the rest dry area. Therefore, the spherical conduction patterns in the solid materials are observed with a “nozzle-shifting” method which requires only two temperature probes. The temperature gradient in the vicinity of the impingement stagnation point is tremendously high, suggesting that the liquid-solid interface temperature is significantly lower than the far-field bulk temperature of the substrate. Moreover, the liquid-to-solid heat transfer is measured, which agrees well with the theoretical prediction. The maximum interface heat flux can reach around 80 W/mm2. It is insensitive to the substrate temperature in a relatively wide temperature range, which brings conveniences to the potential industrial applications.